2022
DOI: 10.3390/su14084839
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Active Learning Classrooms: Impact of Spatial Factors on Students’ Learning Experience and Learning Engagement

Abstract: Previous studies have investigated the spatial attributes of Active Learning Classrooms (ALCs) and their impact on students’ learning experiences and learning engagement independently; however, a holistic investigation of the relationship between these attributes and students’ learning engagement has not been conducted. This study explored how the spatial attributes of ALCs affect students’ learning experiences and learning engagement. An empirical questionnaire was administered to freshmen taking English clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Moreover, research has supported the role of active learning as a superior approach compared to traditional pedagogy [111]. With respect to intrinsic relevance, students studying in active learning classrooms had significantly higher motivation and attitudes toward learning than students studying in traditional classroom layouts [112].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research has supported the role of active learning as a superior approach compared to traditional pedagogy [111]. With respect to intrinsic relevance, students studying in active learning classrooms had significantly higher motivation and attitudes toward learning than students studying in traditional classroom layouts [112].…”
Section: Discussionmentioning
confidence: 99%
“…Answers were rated on a 5-point Likert scale. The dimensional design of the two classroom space satisfaction scales was based on the exploratory factor analysis of the Spatial Factors Affecting Students’ Learning Experience in Classrooms questionnaire conducted by Peng et al (2022) . This questionnaire divided classroom space factors into four dimensions (instructional interaction, furniture perception, learning support, and physical environment) and found that all four dimensions significantly affected students’ learning experience.…”
Section: Survey Methodologymentioning
confidence: 99%
“…A continuación, se relacionan los principales hallazgos relacionados con las diferencias entre usuarios: ◾ Habilidad espacial (HE): con base en la teoría de la carga cognitiva, varios estudios en diversos campos han intentado confirmar o desmentir el supuesto de que los usuarios con alta HE pueden manejar mejor su exposición a un estímulo visualmente complejo y mantener un nivel de esfuerzo mental bajo, en comparación con los usuarios que poseen HE baja [22], [23], [24], [25], [26], [27]. [28], [29]. En la tabla 2 se relacionan los principales efectos en el esfuerzo mental y el desempeño.…”
Section: Impacto De Las Diferencias Entre Usuariosunclassified